1-{3-[(4-Oxopiperidin-1-yl)carbonyl]benzoyl}piperidin-4-one - Rajesh, K.; Vijayakumar, V.; Sarveswari, S.; Narasimhamurthy, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent molecules comprise the asymmetric unit in the title compound, C(18)H(20)N(2)O(4). One of the molecules exhibits disorder in one of its 4-piperidone rings, which is disposed over two orientations [site occupancy of the major component = 0.651 (5)]. The first independent molecule and the minor component of the second disordered molecule are virtually superimposable. The central four C atoms in the major component of the disordered molecule have an opposite orientation. All the 4-piperidone rings have a chair conformation. The carbonyl groups in each molecule have approximate anti conformations [O=C...C=O = 146.2 (2) and -159.9 (2)degrees]. The 4-piperidone rings lie to opposite sides of the central benzene ring in both molecules. In the crystal, molecules are linked by C-H...O interactions. The crystal studied was found to be a non-merohedral twin (twin law -1 0 0, 0 1 0, 0 - 1/2 - 1), the fractional contribution of the minor component being approximately 11%.